The Acadian Migrations - Leblanc, Robert (Cahiers de géographie du Québec)

(untitled) (Département de géographie de l'Université Laval, 1967)
Acadia from its initial settlement in 1604 until 1713 was a part of the French colonial empire in North America. By the Treaty of Utrecht most of Acadia and its French population was ceded to the British. The political instability generated by the anomalous position of the Acadians eventually led to their expulsion in 1755. During the following 50 years their efforts at repatriation were thwarted and only toward the end of the period were they finally settled in places offering a measure of security. The trends of their migrations over the period are illustrated, as well as their final settlement pattern in 1800.